2018
DOI: 10.1063/1.5053489
|View full text |Cite
|
Sign up to set email alerts
|

Design and testing of 3D printed cross compound parabolic concentrators for LCPV system

Abstract: Concentrating Photovoltaic (CPV) Systems has the potential to increase the power output and reduce the cost of PV systems. This work demonstrates a successful attempt to fabricate high performance Cross Compound Parabolic Concentrator (CCPC) using 3D printing. The performance of the 3D printed CCPCs was characterized using a testing setup that consists of a monocrystalline silicon solar cell (10mm x 10mm) mounted on a cooling/rotation stage. Five CCPCs of varied concentration ratio (2.9x, 4.0x, 6.0x, 7.8x and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The use of the CPV system for BIPV application and power generation remains a trending topic for researchers. The compound parabolic concept has been utilized in a handful of studies for solar energy applications [22][23][24][25]. In this study, the concentrator system was fabricated by utilizing a concentrated optic on the top of PSC and assembling it using ultra-violet (UV) curable adhesive.…”
Section: Device Fabrication and Cpv Integrationmentioning
confidence: 99%
“…The use of the CPV system for BIPV application and power generation remains a trending topic for researchers. The compound parabolic concept has been utilized in a handful of studies for solar energy applications [22][23][24][25]. In this study, the concentrator system was fabricated by utilizing a concentrated optic on the top of PSC and assembling it using ultra-violet (UV) curable adhesive.…”
Section: Device Fabrication and Cpv Integrationmentioning
confidence: 99%
“…In recent years, efforts have been reported to investigate CPV systems for building-integrated applications [18][19][20]. One of the research focuses is to improve the performance of the CPC [21][22][23][24][25][26][27][28], including a focus on the optical efficiency, acceptance angle and light uniformity across the PV cell [21][22][23][24]28]. The CPC appears to be a preferred choice over VSC because its compactness and higher concentration ratio [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the half acceptance angle of this concentrator increased to about 40 • due to the light is firstly refracted at entry aperture surface before it is reflected by the parabolic mirrors. The angular response of other types of CPCs have also been investigated [21][22][23][24]. Saitoh et al reported a 3.2x hexagonal CPC that has a half acceptance angle of 32 • [13].…”
Section: Introductionmentioning
confidence: 99%